The Burden of Proof in National Treatment Disputes and the Environment - Henrik Horn (Research Institute of Industrial Economics (IFN), 2009)
The basic legal instrument in the WTO Agreement regulating domestic environmental policies is the GATT National Treatment (NT) provision. The practical ambit of this clause is largely determined by the allocation of the burden of proof (BoP) in NT disputes. The purpose of this paper is to examine the role of this burden for trade liberalization and for the environment, in a situation where imports may cause environmental damage. The paper finds that there may be a tension between NT and environmental concerns, but that this is not likely to arise in the context of severe threats to the environment. In any event, relieving regulating countries of the BoP will have fundamentally unclear implications for the environment.
Keywords: F13; Q56; 330; National treatment; Burden of proof; Environment; GATT; WTO; Trade agreements; WTO-Regeln; Handelsliberalisierung; Umweltpolitik; Umweltverträglichkeit; Zoll; Theorie